2020
DOI: 10.3389/fphar.2020.00667
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Role of Melatonin Against Postmenopausal Bone Loss via Enhancement of Citrate Secretion From Osteoblasts

Abstract: A negative correlation exists between the severity of osteoporosis and citrate levels in bone. Our previous research found that melatonin can significantly improve bone mass in mice with osteoporosis, but the underlying mechanism involving citrate remains unknown. Herein, we demonstrated that melatonin increased bone volume and citrate levels in ovariectomized osteoporosis mice. Melatonin increased citrate and mineralized nodules in osteoblasts induced from primary mouse bone marrow mesenchymal stem cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Although some studies of the effectiveness of MT on menopausal OP have been published, researchers generally have administered MT at the time of ovariectomy (OVX) [ 17 , 19 , 23 , 24 ], or after OP had already become established [ 20 , 25 ]. Systematic analysis of changes in bone mass and bone metabolism with time after OVX was lacking and the effects of MT in different stages of the menopause are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies of the effectiveness of MT on menopausal OP have been published, researchers generally have administered MT at the time of ovariectomy (OVX) [ 17 , 19 , 23 , 24 ], or after OP had already become established [ 20 , 25 ]. Systematic analysis of changes in bone mass and bone metabolism with time after OVX was lacking and the effects of MT in different stages of the menopause are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence indicated the potential role of melatonin in the evaluation of bone mass and strength. Additionally, our previous studies also revealed the positive effect of melatonin on osteoblasts and its therapeutic effect in postmenopausal osteoporosis in animals (Da et al, 2020;Wen et al, 2020). Oral administration of melatonin could increase the serum level of melatonin to improve bone mass (Guan et al, 2022).…”
Section: Introductionmentioning
confidence: 89%
“…The combined product is chemically stable, and free radicals combined with melatonin cannot be regenerated. Our previous study revealed that intragastric melatonin could significantly improve bone mass in postmenopausal mice ( Da et al, 2020 ). Melatonin could enhance osteogenic effects by increasing SIRT1 and SIRT3, the essential factors regulating antioxidant enzyme formation in mitochondria ( Qiu et al, 2019 ; Zhou et al, 2019 ; Chen et al, 2020b ).…”
Section: Antioxidant Substancesmentioning
confidence: 99%